2003
DOI: 10.1002/jnr.10623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tranexamic acid incorporated in fibrin sealant clots on the cell behavior of neuronal and nonneuronal cells

Abstract: Fibrin sealants are commonly used for hemostasis following surgery on various types of tissues. Aprotinin, an effective fibrinolysis inhibitor, is one of the components in some fibrin sealant products currently available. Tranexamic acid (tAMCHA) is another fibrinolysis inhibitor and is used as an alternative to aprotinin. Recent studies on fibrin sealant products containing tAMCHA indicate that it may be responsible for various adverse reactions when used in neurological applications. To determine a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
4
11
0
1
Order By: Relevance
“…LDH levels were significantly higher in the fibrin glue group when compared with the tAMCHA group and higher when compared with the ABStreated group, which is in correlation with the findings of Cox et al 22 who have stated that t-AMCHA is not cytotoxic. Our SEM findings of apoptotic cells in the tAMCHA-treated groups at both time intervals also confirm their results concluding that t-AMCHA used as a fibrinolysis inhibitor has adverse effects on tissue healing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…LDH levels were significantly higher in the fibrin glue group when compared with the tAMCHA group and higher when compared with the ABStreated group, which is in correlation with the findings of Cox et al 22 who have stated that t-AMCHA is not cytotoxic. Our SEM findings of apoptotic cells in the tAMCHA-treated groups at both time intervals also confirm their results concluding that t-AMCHA used as a fibrinolysis inhibitor has adverse effects on tissue healing.…”
Section: Discussionsupporting
confidence: 90%
“…22 In our study, we have found that the number of cells were significantly lower in the Tranexamic acidtreated group when compared with the control group in the both time intervals. They have observed a decrease in adhesion between the cells and detachment from the matrix-coated dishes, leading to an increased cell proliferation rate.…”
Section: Discussionsupporting
confidence: 46%
“…However, we could not verify that cells recover or readhere after incubation in fresh culture medium without t‐AMCA (data not shown). Furthermore, our experiments revealed significant reduction of cellular viability due to incubation with t‐AMCA already within 100 min, compared to 3 days in the other report 22…”
Section: Discussionsupporting
confidence: 46%
“…The concentrations of t‐AMCA, however, achieved due to intravenous administration are in the range of 20–500 μg/mL,21 which is three orders of magnitude less than the concentrations in a commercial fibrin sealant (95 mg/mL). Similarly, reduced proliferation and detachment was already shown earlier for neuronal cells and fibroblasts seeded on polyethyleneimine‐coated culture dishes 22. However, we could not verify that cells recover or readhere after incubation in fresh culture medium without t‐AMCA (data not shown).…”
Section: Discussionmentioning
confidence: 45%
“…TXA inhibits plasminogen, which is ubiquitous in tissue matrix and has numerous functions beyond the cleavage of fibrin. Studies have suggested that TXA may affect cell adhesion, and inhibition of TXA on tumour growth and spread was investigated in the 1970s and 1980s. The authors made the unexpected observation in a previous study that prolonged exposure to high concentrations of topical TXA caused lack of re‐epithelialization, and even epithelial detachment, in an ex vivo human skin wound model.…”
Section: Discussionmentioning
confidence: 99%